Evaluation of Laboratory Findings, Clinical Features and Rates of Diagnosis of Patients Admitted to Outpatient Clinic of Pediatric Neurology with Neuromuscular Manifestations - Uzunhan, Tugce Aksu; Erturk, Biray; Cubuk, Pelin Ozyavuz; Uyanik, BÜLENT; UYANIK, BÜLENT; Ayaz, Akif; Akan, Onur; Ozdemir, Taha Resid (My University, 2020)
Objective: Our aim is to evaluate how many patients with neuromuscular manifestations get a definite diagnosis and which methods are used in the pathway to diagnosis as well as to assess patient characteristics.